Efficacy of new generation herbicide mixtures in irrigated maize (Zea mays) - SIVAMURUGAN, A P; PAZHANIVELAN, S; SUGANTHI, A; BHARATHI, C; RAJU, M; MANIVANNAN, V; KUMARESAN, P (The Indian Journal of Agricultural Sciences, 2024)
The experiment was conducted during rainy (kharif) seasons of 2020 and 2021 at Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu to study the efficacy of new generation herbicide mixtures in irrigated maize (Zea mays L.). The experiment was laid out in a randomized complete block design (RCBD) consisted of 9 treatments including pre-emergence herbicides, new generation post emergence herbicides and other weed management practices [T1, Weedy check; T2, Weed free check; T3, Spraying of atrazine @1 kg/ha as pre-emergence + Hand weeding on 25 DAS (days after sowing); T4, Spraying of atrazine @0.75 kg/ha as pre-emergence + Spraying of topramezone @25.2 g/ha as post-emergence on 25 DAS; T5, Spraying of atrazine @0.75 kg/ha as pre emergence + Tembotrione @120 g/ha on 25 DAS; T6, Spraying of atrazine @1 kg/ha as pre-emergence + Topramezone @25.2 g/ha on 25 DAS; T7, Spraying of atrazine @1 kg/ha as pre-emergence + Tembotrione @120 g/ha on 25 DAS; T8, Spraying of topramezone @25.2 g/ha + atrazine @0.75 kg/ha on 15 DAS; and T9, Spraying of tembotrione @120 g/ha + atrazine @0.75 kg/ ha on 15 DAS], replicated thrice. The results evinced that application of topramezone at 25.2 g/ha + atrazine at 0.75 kg/ha on 15th day after sowing significantly reduced the weed density and dry weight leading to higher weed control efficiency and lower weed index of 62.0% and 3.1%, respectively, during both the years of study. This treatment resulted in higher grain yield (7675 kg/ha), net returns (₹72884/ha) and benefit cost (B:C) ratio (2.33) in irrigated maize.